Dental health economics and diagnosis related groups/casemix in Indonesian dentistry - Ronnie Rivany (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Dental Health Economics is a branch of transdiciplinary science that refers to the Economic and Public Health science. On the other hand, in other developed countries, Diagnosis Related Groups (DRG’s) /Casemix has been used as a basic in creating the same perception between providers, patients and insurance companies in many aspects such as health planning, healthcare financing and quality assurance. Purpose: The objective of this review is to propose a new paradigm of economics to be applied in Indonesian Dentistry. Reviews: The Dental Health Economics should be considered as an important aspect in Indonesian Dentistry, which is used to determine the dental treatment fee based on unit cost, cost containment, and cost recovery rate analysis. Referring to Australian Refined Diagnosis Related Group, health care industry in Indonesia has starting to try a more structured way in grouping disease pattern in order to come up with more precise health care services to their patients. The on going development of Indonesian DRG’s is meant to confirm the disease pattern and partition. Conclusion: The development of Indonesian DRG’s concept, especially the Dental & Oral Disorders, needs a new paradigm, so the practitioners and academics could group and calculate the unit cost from each dental treatment according to the Indonesian DRG version (INA-DRG’s).